If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 73 + -2 = m Combine like terms: 73 + -2 = 71 71 = m Solving 71 = m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 71 + -1m = m + -1m Combine like terms: m + -1m = 0 71 + -1m = 0 Add '-71' to each side of the equation. 71 + -71 + -1m = 0 + -71 Combine like terms: 71 + -71 = 0 0 + -1m = 0 + -71 -1m = 0 + -71 Combine like terms: 0 + -71 = -71 -1m = -71 Divide each side by '-1'. m = 71 Simplifying m = 71
| -4.3=w/-2 | | y+7=7(x+4) | | 1x+6x=10 | | x^2*x*2= | | d/3-10=3.6 | | 9a-7=5(a+9) | | 6(x+3)-10=26 | | -5.2=1.4b | | 7.34+66.4= | | y+7=-3(x+6) | | y-1=(x+5) | | a=0.5c+10 | | 0.16x+0.5=-0.5x-8 | | y+5=-6(x+5) | | y=x^3-6x^2+5x+21 | | y+4=-7(x+7) | | X-4=2/5(3-6x) | | -8p-40=8(1-2p) | | (7^2a^2b^5)^-1/(7^-1a^4b^3) | | -7+8r=-3(r+4)+6r | | .75n+9=n+6 | | 1/5*3/4= | | 2x^3+17x^2+38x+15= | | -7k+27=3+4(-2k+5) | | 4(2x-3)+17=29 | | 10x-5+7x=15-2x+4 | | 1/4x-3=2/5 | | 6x/4-2x | | n-2/7=7 | | 195/100 | | 8(X-2)-5x=46 | | 4(2x-3)+1=29 |